Radioactive contamination of the territory of Belarus: dynamics, current state and long-term forecas - Tsybulka, Mikalai; Germenchuk, Maria; Zhuravkov, Vladislav; Dubailo, Oleg (Journal of the Belarusian State University. Ecology, 2025)
A comprehensive analysis of the dynamics of changes in the radiation situation in the territory of radioactive contamination as a result of the accident at the Chernobyl nuclear power plant has been performed, and a short- and long-term forecast of its changes in the composition and density of radioactive contamination has been given. The information basis of the work was the long-term pollution data of the Republic of 137Cs, 90Sr and 238,239,240Pu obtained as a result of radiation monitoring. In the coming decades (2036 and subsequent) territories belonging to areas of residence with periodic radiation monitoring and with the right to resettlement will account for more than 95% of the entire territory of radioactive contamination. The population will continue to live in these territories. 99.7% of settlements are concentrated here. In the future, there will be a reduction of more than 2.5 settlements in the area with the right to move out and the complete exclusion of settlements in the area of subsequent resettlement. There will be a significant and regular reduction in the areas of subsequent resettlement and with the right to move out. 4. According to the forecast, by 2036, out of 44 administrative districts, radionuclide contamination of the territory of 32 districts will be determined by 137Cs, 3 districts – 137Cs and 90Sr, and the territories of 9 districts – 137Cs, 90Sr and 238-240Pu. In 2046, the territories of 28 districts will be contaminated with 137Cs, 2 districts – 137Cs and 90Sr, and the territories of 9 districts – 137Cs, 90Sr, and 238-240Pu.